Differences in dynamic functional connectivity between naturalistic music listening and rest in preadolescents - Dai, Ruijiao; Toiviainen, Petri; Campo, Fulvia Francesca; Cantou, Pauline; Fasano, Maria Celeste; Kleber, Boris; Vuust, Peter; Brattico, Elvira (Frontiers in Human Neuroscience, 2025)
IntroductionEngagement with music is a significant aspect of adolescents' lives and this interest blossoms during preadolescence. Compared to the extensive body of research focused on adult music brain function, relatively few studies have examined the neural connections involved in music listening among adolescents and preadolescents. This study aims to investigate the dynamic patterns of brain functional connectivity and the transition processes during naturalistic music listening in preadolescents, measuring the transition of brain states from one time point to the next.MethodsWe employed functional magnetic resonance imaging (fMRI) to measure brain activity of 24 healthy preadolescents aged 8 to 12 years during both music listening and rest conditions. Subsequently, we applied a dynamic functional connectivity analysis, Leading Eigenvector Dynamics Analysis (LEiDA), to extract distinct brain states (phase locking patterns) and the corresponding transition processes.ResultsFindings show that occipital brain regions are actively engaged during music listening, possibly linked to attention regulation, visual imagery, and emotional processing. Additionally, we observed a more frequent transition from the default mode network (DMN) state to an orbitofrontal limbic state during music listening, evidencing cognitive shifts that facilitate emotional and reward processing. In contrast, during rest, we obtained a switch to the sensorimotor auditory network, suggesting intrinsic fluctuations in multiple networks.DiscussionThese findings deepen our understanding of subcortical and frontal brain connectivity in preadolescents during music listening, with implications for integrating music into educational practices to support learning and cognitive development.